Hsp70 Is a Novel Posttranscriptional Regulator of Gene Expression That Binds and Stabilizes Selected mRNAs Containing AU-Rich Elements - Kishor, Aparna (American Society for Microbiology, 2013)
The AU-rich elements (AREs) encoded within many mRNA 3′ untranslated regions (3′UTRs) are targets for factors that control transcript longevity and translational efficiency. Hsp70, best known as a protein chaperone with well-defined peptide-refolding properties, is known to interact with ARE-like RNA substrates in vitro. Here, we show that cofactor-free preparations of Hsp70 form direct, high-affinity complexes with ARE substrates based on specific recognition of U-rich sequences by both the ATP- and peptide-binding domains. Suppressing Hsp70 in HeLa cells destabilized an ARE reporter mRNA, indicating a novel ARE-directed mRNA-stabilizing role for this protein. Hsp70 also bound and stabilized endogenous ARE-containing mRNAs encoding vascular endothelial growth factor (VEGF) and Cox-2, which involved a mechanism that was unaffected by an inhibitor of its protein chaperone function. Hsp70 recognition and stabilization of VEGF mRNA was mediated by an ARE-like sequence in the proximal 3′UTR. Finally, stabilization of VEGF mRNA coincided with the accumulation of Hsp70 protein in HL60 promyelocytic leukemia cells recovering from acute thermal stress. We propose that the binding and stabilization of selected ARE-containing mRNAs may contribute to the cytoprotective effects of Hsp70 following cellular stress but may also provide a novel mechanism linking constitutively elevated Hsp70 expression to the development of aggressive neoplastic phenotypes.